A mercapto functionalized magnetic Zr-MOF by solvent-assisted ligand exchange for Hg2+ removal from water. Issue 14 (17th March 2016) - Huang, Lijin; He, Man; Chen, Beibei; Hu, Bin
Abstract : A facile preparation of magnetic MOF composites with flexible mercapto group pendants in their pores is realized through solvent-assisted ligand exchange (SALE) under mild conditions in water, and terephthalate in UIO-66 is replaced with mercaptoacetic acid (MAA). Abstract : A facile preparation of magnetic MOF composites with flexible mercapto group pendants in their pores is realized through solvent-assisted ligand exchange (SALE) under mild conditions in water, and terephthalate in UIO-66 is replaced with mercaptoacetic acid (MAA). After the SALE processing, the crystallinity, porosity, and superparamagnetism of the mercapto functionalized magnetic Zr-MOF (MFC-S) are well maintained, and the obtained MFC-S exhibits a higher adsorption capacity (282 mg g −1 ) for Hg 2+ than that of the magnetic Zr-MOF (MFC-O). Furthermore, the prepared MFC-S can be regenerated easily by liquid desorption after adsorption of metal ions and be reused more than 5 times without obvious decrease in removal performance. The proposed SALE method for the preparation of mercapto functionalized magnetic MOF composites (MFCs) is easy-to-operate and low cost, providing not only a reliable porous MFC platform for the removal of metal ions, but also a simple and efficient synthesis route for the preparation of functionalized MFCs which cannot be achieved through conventional approaches.